2017
DOI: 10.1097/md.0000000000007145
|View full text |Cite
|
Sign up to set email alerts
|

Safety of tumor necrosis factor-alpha inhibitors for treatment of ankylosing spondylitis

Abstract: Background:Ankylosing spondylitis (AS) is a chronic immune-mediated disease affecting the sacroiliac joints and the spine, manifesting with new bone formation and osteopenia. Five tumor necrosis factor-alpha (TNF-α) inhibitors (infliximab, etanercept, adalimumab, certolizumab, and golimumab) are available for the treatment of AS, however, the results for the safety of TNF-α inhibitors in the treatment of AS are not consistent.Methods:In this study, we conducted a meta-analysis to determine the safety of TNF-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
2
30
0
3
Order By: Relevance
“…In contrast to data from randomized controlled trials of patients with RA treated with TNF inhibitors, which indicate an increased risk of discontinuation due to an AE (odds ratio [OR], 1.23; 95% CI, 1.06‐1.43), most meta‐analyses of randomized controlled trials find no evidence of an increased risk of discontinuation due to an AE in patients with ankylosing spondylitis treated with TNF inhibitors. In analyses by Ma et al (3 studies, 1025 participants; risk ratio [RR], 1.97; 95%CI, 0.56‐6.93), by Machado et al 17 (6 studies, 1875 participants; RR, 0.99; 95%CI, 0.98‐1.01) and the most recent one by Hou et al (10 studies, 2984 participants; OR, 1.55; 95%CI, 0.95‐2.54) discontinuations due to AEs in TNF inhibitors group were not significantly different from those treated with placebo in the control group. Only in a Cochrane review, incorporating data from 16 studies (2623 participants), is there moderate quality evidence of an increase in withdrawals due to AE in the TNF inhibitor group vs placebo (OR, 2.44; 95%CI, 1.26‐4.72), though the absolute increase was small (1%; 95%CI, 0‐2%)…”
Section: Drug Survival Ratementioning
confidence: 95%
See 4 more Smart Citations
“…In contrast to data from randomized controlled trials of patients with RA treated with TNF inhibitors, which indicate an increased risk of discontinuation due to an AE (odds ratio [OR], 1.23; 95% CI, 1.06‐1.43), most meta‐analyses of randomized controlled trials find no evidence of an increased risk of discontinuation due to an AE in patients with ankylosing spondylitis treated with TNF inhibitors. In analyses by Ma et al (3 studies, 1025 participants; risk ratio [RR], 1.97; 95%CI, 0.56‐6.93), by Machado et al 17 (6 studies, 1875 participants; RR, 0.99; 95%CI, 0.98‐1.01) and the most recent one by Hou et al (10 studies, 2984 participants; OR, 1.55; 95%CI, 0.95‐2.54) discontinuations due to AEs in TNF inhibitors group were not significantly different from those treated with placebo in the control group. Only in a Cochrane review, incorporating data from 16 studies (2623 participants), is there moderate quality evidence of an increase in withdrawals due to AE in the TNF inhibitor group vs placebo (OR, 2.44; 95%CI, 1.26‐4.72), though the absolute increase was small (1%; 95%CI, 0‐2%)…”
Section: Drug Survival Ratementioning
confidence: 95%
“…None of the meta-analyses of randomized controlled trials of patients with ankylosing spondylitis treated with TNF inhibitors showed an increase in infection and serious infection rates after TNF inhibitors (Table 1). [16][17][18]24,25 Calculated incidence of serious infections after TNF inhibitors was low: 1.9/100 patient-years (pyrs). 24 Also, there was no difference in the occurrence of one of the most common types of infections seen after TNF inhibitors: upper respiratory tract infections (RR, 0.98; 95%CI, 0.93-1.02).…”
Section: Infectionsmentioning
confidence: 99%
See 3 more Smart Citations